Hip moment profiles during circles in side support and in cross support on the pommel horse - Fujihara, T.; Gervais, P. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to analyze the hip moment profiles during Circles and to assess how gymnasts modulate their technique depending on different orientation on the pommel horse. Circles in side support and in cross support performed by six gymnasts were captured using Qualysis motion capture system. Hip joint moments were computed with the assumption that the total leg was a single rigid body. The results implied that the lateral-flexion movement at the hip joint was closely related to the important technique of both types of Circles. Cross-Circles were characterized by the greater flexor moment throughout a Circle and the smaller lateral flexor moment in the rear support phase.